Disposition and metabolism of antibacterial agent, triclocarban, in rodents; a species and route comparison. (1st December 2020) - Waidyanatha, Suramya; Black, Sherry R.; Patel, Purvi R.; Watson, Scott L.; Snyder, Rodney W.; Sutherland, Vicki; Stanko, Jason; Fennell, Timothy R.
Abstract: Triclocarban is a residue-producing antibacterial agent used in a variety of consumer products. These studies investigated the disposition and metabolism of [ 14 C]triclocarban. In male rats following a single gavage administration of 50, 150, and 500 mg/kg, excretion was primarily via feces (feces, 85–86%; urine, 3–6%) with no apparent dose-related effect. In male rats, 29% of the administered dose was excreted in bile suggesting some of the fecal excretion is from the absorbed dose which was excreted to the intestine via bile. The tissue retention of radioactivity was low in male rats (24 h, 3.9%; 72 h, 0.1%). Disposition pattern following gavage administration of 50 mg/kg in female rats and male and female mice were similar to male rats. Plasma elimination half-life of triclocarban in rats following gavage administration was shorter (∼2 h) compared to that based on total radioactivity (≥9 h) which included all products of triclocarban. Absorption following a single dermal application of 1.5 or 3% was low (≤3%) in rodents. Hydroxylated and conjugated metabolites of triclocarban predominated in bile. In hepatocytes, clearance of triclocarban in mouse and human was similar and was faster than in rat.